P111 Is it the time to move towards early histologic diagnosis before surgical management of advanced ovarian cancers?. (1st November 2019) - Akor, W; Oliva, R; Ang, C
Abstract : Introduction/Background: Treatment of advanced ovarian cancer is a combination of surgery and chemotherapy. NICE recommends that a confirmed tissue diagnosis is necessary before the commencement of chemotherapy (NICE CG122, 2011). However, for the surgical treatment of advanced ovarian cancer, there is currently no recommendation for pre-treatment tissue diagnosis. The absence of a histologic diagnosis before surgical treatment could lead to less specificity in the selection of patients receiving surgical intervention. This study was designed to explore the frequency of patients who presented and received treatment for suspected ovarian cancer, who did not have gynaecological cancer. Methodology: A retrospective study was carried out at the Northern Gynaecological Oncology Centre (NGOC), Gateshead the United Kingdom, looking at patient referrals between 2008–2011. Extracted data from electronic patient records was analysed to obtain the frequency of non-gynaecological cancer referrals to the study centre, as well as the types of treatment they received on referral. Results: There were 864 referrals in the study period, of which 764 (88.4%) were confirmed ovarian malignancies. Gastrointestinal malignancies made up 60 (6.9%) of this cohort, breast malignancies 8 (0.9%) and the remaining 32 (3.7%) arising from other sites. Of 704 (81.5%) patients that had surgical treatment, 48 (6.8%) had primary surgery for non-gynaecological cancers undertaken by a Gynae-Oncologist in a gynaecological cancer specialist referral centre. These 48 patients received treatment by a non-specialist in their disease at the first instance, due to a lack of a definitive diagnosis before surgical treatment. Conclusion: Findings from this study, suggests that undertaking a pre-treatment histology for all women regardless of the mode of treatment is imperative in ensuring the appropriateness of intervention by the correct specialist and good patient outcomes. Disclosure: Nothing to disclose.